Breed and season effects on the peri-parturient rise in nematode egg output in indigenous ewes in a cool tropical environment - Tembely, S.; Lahlou-Kassi, A.; Rege, J.E.O.; Mukasa-Mugerwa, E.; Anindo, D.O.; Sovani, S.; Baker, R.L. (Elsevier, 1998)
A study was carried out at the International Livestock Research Institute (ILRI) Debre Berhan Research Station in Ethiopia from 1992 to 1995 to compare the peri-parturient rise (PPR) in faecal nematode egg counts (FEC) in ewes of two indigenous sheep breeds. A total of 1439 Menz and 1347 Horro ewes were single sire mated following oestrus synchronization to lamb in the wet and dry season. Three ewe treatment groups were constituted as mated/lactating/undrenched: mated/lactating/drenched; unmated/undrenched for three wet and three dry lambing seasons. All ewes grazed naturally contaminated pasture. Levels of faecal egg output were monitored at mating, 3 months after mating, 2 weeks befor elambing, 4, 8 and 12 weeks post-parturition in ewes lambing just before the beginning of the dry season (October/November). There was no significant increase in FEC when lambing occurred before the onset of the long rainy season (May/June). The PPR in this study was associated with both lactation and seasonal availability of third-stage infective larvae on pasture. There was no consistent breed difference in FEC during the six sampling periods form mating to weaning. Faecal cultures and worm counts from both breeds confirmed the presence of Longistrongylus (Pseudomarshallagia) elongata, Trichostrongylus spp. and Haemonchus contortus. The role of the peri-parturient rise of FEC in ewes in gastrointestinal nematode transmission is discussed.